Reader, I married him : stories inspired by Jane Eyre - Chevalier, Tracy; Hadley, Tessa; Hall, Sarah, 1974-; Dunmore, Helen, 1952-2017; Gunn, Kirsty; Briscoe, Joanna (Novelist); Gardam, Jane; Donoghue, Emma, 1969-; Hill, Susan, 1942-; Prose, Francine, 1947-; Shafak, Elif, 1971-; Wyld, Evie; et al. (William Morrow, an imprint of HarperCollins Publishers, 2016)
This collection of original stories by today's finest women writers--including Tracy Chevalier, Francine Prose, Elizabeth McCracken, Tessa Hadley, Audrey Niffenegger, and more--takes inspiration from the opening line in Charlotte Brontë's most beloved novel, Jane Eyre. A fixture in the literary canon, Charlotte Brontë is revered by readers all over the world. Her novels featuring unforgettable, strong heroines still resonate with millions today. And who could forget one of literature's best-known lines: "Reader, I married him" from her classic novel Jane Eyre? Part of a remarkable family that produced three acclaimed female writers at a time in nineteenth-century Britain when few women wrote, and fewer were published, Bronté has become a great source of inspiration to writers, especially women, ever since. Now in Reader, I Married Him, twenty of today's most celebrated women authors have spun original stories, using the opening line from Jane Eyre as a springboard for their own flights of imagination.